Characterisation of aciplex membrane by x-ray photoelectron spectroscopy - Abu Bakar Mohamad; Wan Ramli Wan Daud; Amir Kadhum; Fathi Messaud; Mohd. Ambar Yarmo (Universiti Kebangsaan Malaysia, 1997)
Chemical structure of treated and untreated Aciplex membrane has been studied by X-ray Photoelectron Spectroscopy (XPS). Survey spectra showed that both membrane surfaces consist of Fluorine, Carbon, Oxygen, Sulphur and trace of Titanium. Binding energies for the elements are (C1s at 290.6 eV, F1s at 687.5 eV, O1s at 531.3 eV, S2P at 168.1 eV and Ti2P at 454.4 eV). Analysis of narrow scan XPS-spectra of each element demonstrate the presence of (-CF, -CF2, CF3, C-O-C and SO-3) groups, which are in agreement with the structural formula as disclosed by the manufacturer. There is no significant change in chemical states of untreated and treated membrane, which reflect its stability to treatment conditions.